Born for the muses: the life and masses of Jacob Obrecht - Wegman, Rob C. (Oxford Clarendon Press, 1994)
Son of a town trumpeter, Jacob Obrecht became one of the most prominent composers in Europe in the late fifteenth century. In Born for the Muses, Rob Wegman enlarges our picture of the social and cultural conditions that framed his world, drawing on a wealth of new archival sources and a newly discovered dated portrait that sheds light on his development as a composer. Obrecht's greatest contribution lay in the field of mass composition. In a penetrating stylistic analysis, Wegman treats each of the thirty-odd surviving masses as a historical record, tracing influences and establishing a rich context for the development of Obrecht's musical language. This new assessment of his creative achievement and historical significance entirely changes the face of Obrecht studies and of late fifteenth-century music in general.